Spelling patterns : structure, sight, sound - Johnson, Mary R. (Educators Pub. Service, 1988)
A workbook based on 2 spelling techniques: the basic vertical visual spelling patterns and the critical handwritten neuromuscular reinforcement. For grade 7 and up.